Strategi Pembelajaran Peserta Didik Penyandang Autis dalam Berinteraksi Sosial di MI Muhammadiyah PK Kartasura - Pramesti, Agita Indah; Wulandari, Murfiah Dewi (PAKAR Pendidikan, 2023)
Education for learners with special needs, especially autism, is necessary for the survival of society. Therefore, this research has several objectives, among others, to find out: 1) Learning planning for students with autism; 2) Implementation of learning for students with autism; 3) Evaluation of learning for students with autism; 4) Obstacles and solutions for learning students with autism at MI “Muhammadiyah Special Program Kartasura” towards improving their ability to interact socially. The type of descriptive qualitative research applied in this study. Data collection techniques were obtained from direct observation, interviews with informants to provide details about the object under study, and documentation. Data validity used is triangulation, extended observation, and peer checking. The results of this study prove: 1) Learning planning is structured in the Individual Learning Planning (I.L.C.) sheet. 2) The implementation of learning by teachers includes learning approaches, learning strategies, learning methods, various learning media, and cooperation with the teachers concerned in implementing learning. 3) Learning evaluation for autistic students is divided into learning outcomes and developmental assessments. 4) Obstacles during the learning process are controlling emotions, focusing on autistic students, and sensory integration problems of autistic students. Solutions solved by teachers from the obstacles listed are controlling the emotions of autistic students, restoring the focus of autistic students, and improving the sensory integration barriers of autistic students with therapy.